Presence of a prothrombotic state in people with idiopathic pulmonary fibrosis: a population-based case-control study - Navaratnam, Vidya; Fogarty, Andrew W.; McKeever, Tricia M.; Thompson, Norma; Jenkins, Gisli; Johnson, Simon R.; Dolan, Gerard; Kumaran, Maruti; Pointon, Kate; Hubbard, Richard B. (BMJ Publishing Group, 2014)
BACKGROUND: Laboratory studies suggest that the clotting cascade is activated in fibrotic lungs. Since humans vary in their tendency to clot due to a variety of inherited or acquired defects, we investigated whether a prothrombotic state increases the chance of developing idiopathic pulmonary fibrosis (IPF) and/or worsens the prognosis of IPF.